Hereditary thrombophilia by factor V Leiden G1691A (heterozygous) and FII prothrombin G20210A (homozygous) mutations in a patient with ischemic cerebrovascular accident - Leonardo G. P. Ruiz; Maria Gabriela L. Oliveira; Adriana L. Z. Ruiz; Camila S. Daher; Mauricio L. Nogueira (Sociedade Brasileira de Patologia Clínica, 2018)
ABSTRACT Mutations related to Factor V Leiden (G1691A) and prothrombin (G20210A) are associated with a significantly increased risk of venous thromboembolism. The identification of a patient affected by episodes of venous thromboembolism and carrier of G1691A (heterozygous) and G20210A (homozygous) polymorphisms was determined by molecular tests [real-time polymerase chain reaction (PCR) methodology, Genexpert system] during attendance at the Base Hospital of São José do Rio Preto-SP, Brazil.